Re-conceptualizing Public Relations Practices in Nigeria: A Framework to Address Systemic Challenges - Eyo, Nsini Anselem (LSPR Institute of Communication & Business, 2025)
This conceptual paper examines the roles and challenges of public relations practice in Nigeria by proposing a framework to address systemic issues hindering its professionalization. Despite cultural diversity shaping PR globally, the practice in Nigeria faces significant obstacles, including limited strategic involvement, deployment of unqualified practitioners, political interference, inadequate education and training, weak ethical standards, and lack of a robust regulatory framework. The absence of autonomy by the Nigerian Institute of Public Relations (NIPR) further exacerbates these issues, allowing individuals without formal training or specialization to practice, thereby undermining the profession's credibility. Using a narrative literature review, the study synthesizes existing research to identify gaps and develop a conceptual framework aimed at addressing these challenges. Drawing from role theory in public relations and Grunig’s Excellence theory, the paper proposes a tripartite framework for PR professionalization in Nigeria. This framework emphasizes education to impart theoretical knowledge and practical skills, accreditation to ensure eligibility for membership and registration, and certification to uphold ethical standards and professional conduct as well as autonomy of the NIPR as the primary regulatory body of the procession in the country. By implementing this tripartite model, PR practitioners in Nigeria can be empowered to perform strategic managerial and operational communication roles effectively. This will enable practitioners and by extension NIPR to uphold the integrity of the profession, and foster standardization and professionalization in alignment with global best practices. Hence, this study provides actionable insights for re-conceptualizing PR in Nigeria, advancing its role as a credible and strategic profession.